Identification of Flavonoid Compounds in Clove Leaves (Syzygium aromaticum (L.) L.M. Perry) Using Thin Layer Chromatography Method - Nisa, Eliza Choirun; Mulatasih, Endah Ratnasari; makhdalena, makhdalena; Hartati, Ani; Fauziyah, Ageng Hasna (Journal of Agritechnology and Food Processing, 2025)
Clove (Syzygium aromaticum (L.) L.M.Perry) is a plant that has been used for centuries in traditional medicine for many ailments. Clove leaves contain saponins, tannins, alkaloids, glycosides and flavonoids. Flavonoids are phenolic compounds that can change color when a base or ammonia is added so they are easily detected using thin layer chromatography. Identification of flavonoid compounds contained in clove leaves (Syzygium aromaticum (L.) L.M.Perry) was carried out using the thin layer chromatography method. This research is intended to identify the flavonoid content in clove leaves. The method used to identify flavonoids from the flavones, flavonols, glycoflavones and biflavonyl groups uses thin layer chromatography.The organoleptic results of clove leaf simplicia have a brownish green color, a distinctive pungent odor, and are in the form of a rather fine powder. Flavonoid phytochemical screening had positive results indicated by the presence of an orange color on the amyl alcohol layer. Then the clove leaf simplicia was prepared for testing using thin layer chromatography by heating using 2N HCl at a temperature of 100 oC and extracted with ethyl acetate then spotted on a thin layer chromatography plate. The organoleptic results of the clove leaf extract had a reddish brown color, with a sticky texture and no smell. Examination of clove leaf extract (Syzygium aromaticum (L.) L.M.Perry) using thin layer chromatography, this elution was carried out using an acidic eluent, showing that clove leaves were positive for flavonoids in the flavon group which showed a faint brown color with Rf 0.66 and 0,70 and negative for flavonoids in the flavonol, glycoflavone and biflavonyl groups because the Rf value and stain color do not match comparisons in the literature.